Insights on historical milestones of mental health in Nepal: Country profile - Gayatri Khanal; Y. Selvamani; Prabhat Sapkota (Indian Journal of Psychiatry)
The present paper has highlighted the mental health development in Nepal. It covers the current state of mental health system and services and a throwback on the significant changes over a period of time. This review grabs a sneak into mental health plan/policies, prevalence; health facilities and human resources, monitoring and supervision, budget allocation, nongovernmental sector involvement, and international agreements. Every description in this paper is substantially based on the progression made at the different time frames, which provides clear understanding of the mental health situation in Nepal. Furthermore, this article throws insights on the main challenges to overcome the current situation on mental health and the associated treatment gap due to stigma toward mental illness, lack of appropriate budget allocation, shortage of human resources, and fear of discrimination.